English for Academic Purposes in EFL Contexts: The Needs for Integrating Reading and Writing Skills - Kusni Kusni (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
This paper aims at discussing an interesting issue about the needs for integrating reading and writing skills in English for Academic Purposes (EAP) in EFL contexts. After experiencing teaching several EAP courses, I come to a conclusion that the integration of reading and writing skills is the most crucial and significant objective of teaching English at several study programs at universities in EFL contexts. In order to know how to do this, in this ideational paper, I share ideas to all readers the bases and reasons behind the ideas, the types of tasks for the integration, and some problems as well as challenges of the integration. I focus my analysis firstly on the significant roles and reasons of both skills to be integrated in accordance to some research findings. Secondly, I present readers problems and challenges in integrating reading and writing in EAP classroom. At last, this paper discusses the types of tasks the students should do in integrating these most important academic skills.